(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Most of the patients of psoriasis have a chronic course withthe need for continuous control of disease activity. Patientswith moderate-to-severe disease generally requirephototherapy, photo-chamotherapy or systemic agents (e.g.cyclosporine, methotrexate, oral retinoids, fumaric acidesters) to control their disease adequately. In general thesetherapeutic modalities have proven to be highly effective inthe treatment of psoriasis. However, potentially serious toxicitycan limit their long term use. In this respect, hydroxyureacompares favourably with methotrexate which has a potentialfor producing irreversible hepatic damage and cyclosporineA with its potential for dose-related nephrotoxicity.Hydroxyurea, a hydroxylated molecule of urea is commonlyused to treat chronic myelogeneous leukemia andpolycythemia vera. Recent studies suggest it as an alternativeto methotrexate in moderate-to-severe psoriasis. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11330 J Bangladesh Coll Phys Surg 2011; 29: 219-226